2021
DOI: 10.1371/journal.pone.0249893
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of wild and mass-reared populations of a generalist aphid parasitoid and improvement of biological control

Abstract: Due to their ability to parasitize various insect species, generalist parasitoids are widely used as biological control agents. They can be mass-reared and released in agroecosystems to control several pest species in various crops. However, the existence of genetic differentiation among populations of generalist parasitoid species is increasingly recognized and this can be associated with an adaptation to local conditions or to a reduced range of host species. Moreover, constraints of mass-rearing conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…It is common that natural enemies that were never deployed by the grower establish themselves in a greenhouse (e.g. Bosco et al, 2008 ; Gavkare et al, 2014 ; Postic et al, 2021 ). It has been shown that the presence of both specialist and generalist parasitoids can stabilize biological control (Raymond et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is common that natural enemies that were never deployed by the grower establish themselves in a greenhouse (e.g. Bosco et al, 2008 ; Gavkare et al, 2014 ; Postic et al, 2021 ). It has been shown that the presence of both specialist and generalist parasitoids can stabilize biological control (Raymond et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only Aphidius microlophii Pennacchio and Tremblay has been split from A. ervi and described as a specialized parasitoid of Microlophium carnosum (Buckton), associated with Urtica spp., which are common in cultivated areas [95,96]. Molecular markers did not support any significant differentiation within the "ervi" complex [97]. This issue should be further investigated with more robust taxonomic and geographic samples.…”
Section: Species Complexesmentioning
confidence: 97%
“…Nevertheless, the amount of genetic variation for biological control traits is currently poorly investigated and remains largely unknown (Ferguson, 2020; Lirakis & Magalhães, 2019; Wajnberg, 2004). Only 2.4% of the studies investigating genetics of biocontrol traits reported information on genetic variation (e.g., Postic et al, 2021). Characterizing the genetic architecture of biocontrol traits is important because the success of artificial selection often depends on the number and location of the loci involved, and their interactions such as dominance, epistasis, and pleiotropy (Leung et al, 2020).…”
Section: Human Manipulations Of Evolution: Genetic and Evolutionary A...mentioning
confidence: 99%